ANALISIS PENGARUH PENERAPAN METODE LISTENING DALAM UJIAN SEKOLAH TERHADAP PENINGKATAN KEMAMPUAN MENDENGARKAN DAN PEMAHAMAN MATERI SISWA SMA - Syaharani, Azzahra (Universitas Islam Malang, 2023)
The purpose of this study was to analyze the effect of applying the listening method in school exams to improving high school students' listening skills and material comprehension. The research method used is a literature study that involves searching and analyzing literature related to previous research. This study aims to collect information and findings from previous studies that have discussed the use of the listening method in school exams and its impact on high school students' listening skills and material comprehension. The results of this study indicate that the application of the listening method in school exams has a significant positive effect on increasing high school students' listening skills and material comprehension. Based on the analysis of the literature, the listening method can help students improve their listening skills better, improve understanding of subject matter, and develop critical thinking skills. In addition, the use of the listening method in school exams can also motivate students to be actively involved in the learning process and improve information retention. Keywords: listening method, school exams, listening skills, understanding of the material